Absence of vitamin D receptor (VDR)‐mediated PPARγ suppression causes alopecia in VDR‐null mice. Issue 3 (8th December 2016) - Saini, Vaibhav; Zhao, Hengguang; Petit, Elizabeth T.; Gori, Francesca; Demay, Marie B.
ABSTRACT: Vitamin D receptor (VDR) mutations in humans and mice cause alopecia. VDR‐null (VDR −/− ) mice exhibit lack of postmorphogenic hair cycles as a result of impaired keratinocyte stem cell (KSC) function. To identify the molecular basis for abnormal KSC function, RNA sequencing of wild‐type (WT) and VDR −/− KSCs was performed. These studies demonstrated that >80% of differentially expressed genes are up‐regulated in VDR −/− KSCs; thus, the VDR is a transcriptional suppressor in WT KSCs. Peroxisome proliferator‐activated receptor γ ( PPARγ ), PPARγ coactivator 1β ( PGC1β ), and lipoprotein lipase ( LPL ) were among the up‐regulated genes identified. Chromatin immunoprecipitation analyses demonstrated that these genes are direct VDR targets in WT keratinocytes. Notably, VDR occupancy of the PPARγ regulatory region precludes PPARγ occupancy of this site, based on the observation that PPARγ interacts with these sequences in VDR −/− but not WT keratinocytes. This contrasts with the VDR and PPARγ co‐occupancy observed on PGC1β and LPL gene regulatory regions identified. Studies in mice with keratinocyte‐specific PPARγ haploinsufficiency were performed to identify the functional consequences of enhanced PPARγ expression. PPARγ haploinsufficiency normalized PPARγ mRNA levels in VDR −/− keratinocytes and restored anagen responsiveness in vivo in VDR −/− mice, resulting in hair regrowth. Thus, absence of VDR‐mediated PPARγ suppression underlies alopecia in VDR −/− mice.—Saini, V., Zhao, H., Petit, E. T., Gori, F., Demay, M. B. Absence of vitamin D receptor (VDR)‐mediated PPARγ suppression causes alopecia in VDR‐null mice. FASEB J. 31, 1059–1066 (2017). www.fasebj.org